1994
DOI: 10.1093/oxfordjournals.aje.a117317
|View full text |Cite
|
Sign up to set email alerts
|

Use of Sunbeds or Sunlamps and Malignant Melanoma in Southern Sweden

Abstract: In a population-based, matched case-control study from the South Swedish Health Care Region, which has the highest risk for melanoma in Sweden, the relation between the use of sunbeds or sunlamps and malignant melanoma was investigated. Between July 1, 1988, and June 30, 1990, a total of 400 melanoma patients and 640 healthy controls aged 15-75 years answered a comprehensive questionnaire containing different epidemiologic variables. Questions regarding the use of sunbeds or sunlamps were included. The odds ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
72
2
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(83 citation statements)
references
References 0 publications
8
72
2
1
Order By: Relevance
“…The present results are in accordance with our previous results from South Sweden (Westerdahl et al, 1994), as well as results from Scotland (Swerdlow et al, 1988), Canada (Walter et al, 1990), and Belgium, France and Germany (Autier et al, 1994). All these studies have mainly come from areas with relatively low ambient UV radiation.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The present results are in accordance with our previous results from South Sweden (Westerdahl et al, 1994), as well as results from Scotland (Swerdlow et al, 1988), Canada (Walter et al, 1990), and Belgium, France and Germany (Autier et al, 1994). All these studies have mainly come from areas with relatively low ambient UV radiation.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have shown similar results (Chen et al, 1998;Swerdlow et al, 1988;Walter et al, 1990;Westerdahl et al, 1994). These findings may not be surprising since sunbed use is particularly common in teenagers and young adults (Boldeman et al, 1996) and the high OR might then be due to the high exposure in this age group per se.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Beral et al (1982) and Walter et al (1992) reported increased risks of melanoma amongst workers exposed to fluorescent lighting. Swerdlow et al (1988), Walter et al (1990) and Westerdahl et al (1994 found significantly elevated risks of cutaneous melanoma associated with sunlamp use. Elwood et al (1986) found a significantly increased risk of cutaneous melanoma amongst workers exposed to light from welding torches, printing lights and other sources of ultraviolet light.…”
mentioning
confidence: 98%